Unveiling the molecular mechanism of sepal curvature in Dendrobium Section Spatulata through full-length transcriptome and RNA-seq analysis - Qu, Xuefeng; Li, Na; Xu, Cong; Huang, Zifeng; Li, Chunyan; Jiang, Yang; Zheng, Guizhao; Fu, Haiping; Zhang, Guangyan; Liu, Chuan (Frontiers in Plant Science, 2024)
Introduction Orchids are renowned for their intricate floral structures, where sepals and petals contribute significantly to ornamental value and pollinator attraction. In Dendrobium Section Spatulata, the distinctive curvature of these floral organs enhances both aesthetic appeal and pollination efficiency. However, the molecular and cellular mechanisms underlying this trait remain poorly understood. Methods Morphological characteristics of five hybrids were analyzed, with a particular focus on hybrid H5, which exhibits pronounced sepal curling. Full-length transcriptomic sequencing was employed to assemble a reference transcriptome, while RNA-seq identified differentially expressed genes (DEGs) between sepals and petals. Gene ontology and pathway enrichment analyses were conducted to uncover biological processes associated with sepal curvature. Cytological microscopy was used to examine cell size and number, and quantitative real-time PCR (qRT-PCR) was performed to validate transcriptomic findings. Results The reference transcriptome contained 94,258 non-redundant transcripts, and RNA-seq identified 821 DEGs between sepals and petals, with 72.8% of these upregulated in sepals. Enrichment analysis revealed the significant involvement of DEGs in cytokinesis, cytoskeletal organization, and energy metabolism. Notably, myosin II filament organization was implicated in generating the mechanical forces responsible for curling, while metabolic pathways provided the energy necessary for these developmental processes. Cytological observations showed that the upper cell layers of the sepal were smaller and more numerous than the lower layers, indicating that differential cell growth contributes to sepal curvature. qRT-PCR analysis validated the differential expression of selected genes, supporting the transcriptomic findings. Discussion The interplay of cellular mechanics, cytoskeletal dynamics, and metabolic regulation is crucial in shaping sepal morphology. Future studies involving gene knockdown or overexpression experiments are recommended to validate the roles of specific genes in processes such as actin organization and myosin activity. Such work would provide deeper insights into the contributions of cytoskeletal dynamics and mechanical force generation to sepal morphogenesis.